Determinants of information system effectiveness in managing agro-based projects - Thi, Lip Sam; Wan Adnan, Che Wan Muhammed Salleh (Universiti Malaysia Sarawak, 2016)
Previous studies have suggested the use of PMIS is considered to be advantageous towards successful project management.Using the antecedents of system success model proposed by DeLone and McLean, and the updated Information System Success Model (ISSM), this study attempts to examine the implementation of PMIS in agro-based projects undertaken by the Ministry of Agriculture and Agro-based Industry in Malaysia (MoA).The objectives of the study are to examine PMIS effectiveness and identify the determinants that influence system effectiveness.The sample for this study comprised of PMIS end-users from MoA. The findings of this study indicate that PMIS is an effective system to support end users for project management and monitoring activities.Information and service quality have significant relationship with system effectiveness.Between these factors, information quality is found to have the greatest effect on the variation of PMIS effectiveness.